PENGARUH BAHAN TAMBAH RD260, E7016, ER705-6 PADA PENGELASAN OXY- ACETYLENE TERHADAP KEKUATAN TARIK PADA PLAT BORDES TIPE ST-37 - Didik Setiawan; Wawan Trisnadi Putra; Nanang Suffiandi Ahmad (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to test the performance of the steering system, transmission, and electric braking system of the Urban Concept Warek V.1.1 type. The basic assumption of electricity is designed with the Urban Concept type (four vehicles like the current car) which is adjusted to the regulations for the Energy Saving Petite Contest (KMHE), which is held by the Indonesian government through the Ministry of Research, Technology and Higher Education. In the steering system design using the Ackerman type steering system, the transmission system uses a chain deive differential while the braking system uses hideelik discs. In the test results, the steering system has a maximum turning angle of 45 ° with a radius of less than 6 meters, for the transmission system in the test engine rotation speed (n,) is 589,867 rpm and electric meter rotation is 642.6 rpm with average speed - Average. 53 km / hour. The amount of deceleration of the braking system is 4.901 and 1.47 s for the braking time.